2017
DOI: 10.1371/journal.pone.0178103
|View full text |Cite
|
Sign up to set email alerts
|

Psychosine enhances the shedding of membrane microvesicles: Implications in demyelination in Krabbe’s disease

Abstract: In prior studies, our laboratory showed that psychosine accumulates and disrupts lipid rafts in brain membranes of Krabbe’s disease. A model of lipid raft disruption helped explaining psychosine’s effects on several signaling pathways important for oligodendrocyte survival and differentiation but provided more limited insight in how this sphingolipid caused demyelination. Here, we have studied how this cationic inverted coned lipid affects the fluidity, stability and structure of myelin and plasma membranes. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 69 publications
1
37
0
Order By: Relevance
“…For instance, using RBCs and oligodendrocytes, they showed that psychosine disrupts SM-enriched domains and increases the rigidity of local PM areas while promoting the shedding of MVs. Areas of higher rigidity have been confirmed in Twitcher myelin and correlate with higher contents in psychosine and myelin microvesiculation [ 180 ] (see also Section 5.3.5 ).…”
Section: Microvesicle Biogenesis and Shedding—role Of Plasma Membrmentioning
confidence: 95%
See 1 more Smart Citation
“…For instance, using RBCs and oligodendrocytes, they showed that psychosine disrupts SM-enriched domains and increases the rigidity of local PM areas while promoting the shedding of MVs. Areas of higher rigidity have been confirmed in Twitcher myelin and correlate with higher contents in psychosine and myelin microvesiculation [ 180 ] (see also Section 5.3.5 ).…”
Section: Microvesicle Biogenesis and Shedding—role Of Plasma Membrmentioning
confidence: 95%
“…For example, in Krabbe disease, the abnormal accumulation of psychosine in the oligodendrocyte membrane disrupts lipid rafts [ 179 ]. This leads to the disruption of several signaling pathways but also to an increased rigidity of localized areas promoting the shedding of MVs [ 180 ], thought to be essential in the demyelination observed in this disease (see also Section 5.1 ).…”
Section: Microvesicle Biogenesis and Shedding—role Of Plasma Membrmentioning
confidence: 99%
“…Although caused by mutations in either of the genes of NPC1 or NPC2 proteins involved in cholesterol transport out of lysosomes, Niemann‐Pick type C disease also leads to sphingolipids accumulation in late endosomes/lysosomes. Toxic sphingolipids such as sulfatides or psychosine have been shown to accumulate in some sphingolipidoses and to be secreted with EVs . The cellular ceramide content has also been shown to be regulated by exosome secretion through adiponectin binding to T‐cadherin .…”
Section: Exosomes and Homeostasismentioning
confidence: 99%
“…Toxic sphingolipids such as sulfatides or psychosine have been shown to accumulate in some sphingolipidoses and to be secreted with EVs. 118,119 The cellular ceramide content has also been shown to be regulated by exosome secretion through adiponectin binding to Tcadherin. 120 Adiponectin is a protein secreted by adipocytes as oligomers that bind to T-cadherin, a unique GPI-anchored form of cadherin notably present in lipid rafts of endothelial vascular cells.…”
Section: Lipidsmentioning
confidence: 99%
“…A recent study revealed a role for the GSL, galactosyl-Sph, and its metabolic enzyme, galactosyl-CDase, in the control of plasma membrane structure and EV shedding. D'Auria et al (98) highlighted the involvement of galactosyl-Sph in alteration of membrane organization and microvesiculation from oligodendrocytes, the glial cell type that deposits myelin along neuronal axons in the central nervous system.…”
Section: Galactosyl-sph-dependent Ev Biogenesismentioning
confidence: 99%